The influence of intellectual capital, good corporate governance and accounting conservatism on company’s financial performance - Rika Regina (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
Purpose - This research aimed to determine the effect of intellectual capital, good corporate governance (board of commissioners, independent commissioners and managerial ownership) and accounting conservatism on company financial performance (study of companies listed on the Jakarta Islamic Index (JII) in 2017-2019).Method - The population in this research was 42 companies registered in JII 2017-2019. Purposive sampling method was used for sample selection and 16 companies were selected. This research used secondary data with multiple regression model data analysis.Result - The results of this research stated that intellectual capital had a positive and significant effect on the company's financial performance. Good corporate governance as measured by the board of commissioners, independent commissioners and managerial ownership had a negative but insignificant effect on the company's financial performance, and accounting conservatism had a positive but insignificant effect on the company's financial performance.Implication - Companies registered in JII are advised to improve the financial performance of their companies, especially those listed in 2017-2019.Originality - The secondary data sources used in this research were obtained from the official website of the Indonesia Stock Exchange (BEI), namely www.idx.co.id.